BISNIS DALAM MASYARAKAT JEPANG - Maharani Ratna Patria (IZUMI, 2015)
this journal explains customs in doing business with Japanese. Japanese has several unique etiquettes which is unknown by westerns. Those customs are important to explain, to avoid missed perception between Japanese and western businessman. This journal also gives some tips for those who don’t really understand Japanese, so that they can adapt with them. This journal explains some Japanese way of life that are applied in their way of doing business. Japanese way of life explanations are highly expected understood so that one understands Japanese behave in doing bussines. For instance: TQM, kaizen, and kaisan are just some of Japanese way of life that is explained simply in this journal.